Characterization of Rosé Table Wines made in Planalto Norte Catarinense, harvest 2022 - Palinguer, Rodrigo; Wisniewski, Caroline de Souza; Demetrio, Kelly Eduarda; Farias, Eduardo Virmond Souza; Steidel, Otávio Frederico Tschoeke; Jansen, Thuany Aparecida Levandoski; Kowal, Alcemir Nabir; Schmidt, Eduarda; Maciel, Thalia Aparecida Silva; Almeida, Rabechlt Stange; et al. (Revista de Ciências Agroveterinárias, 2024)
Carrying out physical chemical analyzes is necessary to have an idea of the adequate standards of the wines. In this context, the aim of this work is to carry out the physical-chemical characterization of samples of Rosé Table Wines produced in the North Plateau of Santa Catarina. The present work was carried out in the 2022 harvest, at the Fruticulture Laboratory of the Federal Institute of Santa Catarina - Campus Canoinhas, and the physicochemical characterization. In all, eight samples of wines of this category were collected from the municipalities of Itaiópolis Canoinhas, Papanduva and São Bento do Sul. It was evaluated: total acidity (meq L-1), pH, relative density, soluble solids (ºBrix), color intensity and color tone. The data were typed, tabulated and with the help of the Excel 2010 software, the tables were prepared to carry out a descriptive analysis of the data obtained in the evaluated samples. The data referring to the characterization of the physical-chemical profile of Rosé Table Wines, demonstrate the potential of the Planalto Norte Catarinense for the elaboration of wines. The observed values are in accordance with the current legislation; however, it is necessary to improve elaboration methods, especially related to the intensity and color tone of the wines, which in the present study showed a high unevenness between the samples.